Cold-rolled steel plate and method for producing cold-rolled steel plate
A cold-rolled steel plate with a tailored chemical composition and heat treatment process achieves high strength and excellent processing by creating a fine-grained microstructure with controlled phase distributions, addressing the limitations of existing manufacturing methods.
Patent Information
- Application Number
- JP2023119064
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-07-21
- Publication Date
- 2025-01-31
AI Technical Summary
Existing methods for manufacturing steel plates fail to achieve a balance between high strength and excellent processing properties, particularly in automotive parts, where the microstructure and composition of the steel plates do not effectively combine to meet these requirements.
A cold-rolled steel plate with a specific chemical composition and controlled heat treatment process, including rapid heating to an austenite single-phase region, followed by rapid cooling and brief holding at a two-phase region, to create a microstructure with fine ferrite and hard phases like Martensite or Bainite, ensuring a balanced strength and processing performance.
The method produces a cold-rolled steel plate with enhanced tensile strength, ductility, and formability, achieving mechanical properties that surpass conventional methods by maintaining a fine-grained microstructure with controlled phase distributions.
Smart Images

Figure 2025016052000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a cold-rolled steel sheet and a method for producing the cold-rolled steel sheet. [Background technology]
[0002] Steel sheets used for automobile parts and the like are required to have high strength as well as excellent formability.
[0003] Japanese Patent No. 4292986 describes a method for manufacturing a high-tensile steel sheet. This manufacturing method is characterized in that a cold-rolled sheet that has been subjected to cold rolling is heated to an annealing temperature in the temperature range of (Ac3 transformation point -50°C) to (Ac3 transformation point +100°C) with an average heating rate of 0.5 to 3°C / s above the Ac1 transformation point, and then cooled to a predetermined cooling stop temperature Ts at an average cooling rate of 30 to 100°C / s and retained in the predetermined temperature range for 50 seconds or more.
[0004] Japanese Patent No. 6119655 describes a high-strength galvannealed steel strip with excellent formability and small material variation within the strip. This high-strength galvannealed steel strip is characterized in that the microstructure of the steel sheet contains, in area ratio, 50% or more of ferrite, 5 to 30% of martensite, 2 to 8% of pearlite, and 2 to 15% of retained austenite, with a tensile strength (TS) of 780 MPa or more, a strength-elongation balance (TS×El) of 20,000 MPa·% or more, a hole expansion ratio (λ) of 35% or more, a yield ratio (YR) of 60% or less, and a difference between the maximum tensile strength and the minimum tensile strength within the strip of 50 MPa or less.
[0005] Japanese Patent No. 7006849 discloses a steel sheet, which has a steel structure with the following area ratios: ferrite: 40% to 70%, the total of bainite and tempered martensite: 5% to 30%, retained austenite: 4% to 18%, fresh martensite: 8% to 35%, and the remainder: 55% or less, in which cementite particles are present in the retained austenite, the ratio of the area ratio of the cementite particles to the area ratio of the retained austenite is 5% to 25%, and the tensile strength is 780 MPa or more and less than 980 MPa. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] Patent No. 4292986 [Patent Document 2] Patent No. 6119655 [Patent Document 3] Patent No. 7006849 Summary of the Invention [Problem to be solved by the invention]
[0007] An object of the present invention is to provide a cold-rolled steel sheet having high strength and excellent formability. [Means for solving the problem]
[0008] A cold rolled steel sheet according to an embodiment of the present invention has a chemical composition, in mass%, of C: 0.03 to 0.30%, Si: 0.05 to 1.00%, Mn: 0.10 to 3.00%, P: 0.050% or less, S: 0.020% or less, Al: 0.010 to 0.100%, N: 0.0100% or less, at least one of Ti and Nb: 0.020 to 0.150% in total, and the balance: Fe and impurities, and has a metal structure containing 60% by volume or more of ferrite and at least one of martensite and bainite in a total amount of 5% by volume or more and less than 30% by volume, and an average crystal grain size d of the ferrite. F is 10.0 μm or less.
[0009] The cold rolled steel sheet according to one embodiment of the present invention has a chemical composition, in mass%, of C: 0.03 to 0.30%, Si: 0.05 to 1.00%, Mn: 0.10 to 3.00%, P: 0.050% or less, S: 0.020% or less, Al: 0.010 to 0.100%, N: 0.0100% or less, at least one of Ti and Nb: 0.020 to 0.150% in total, and further includes Cr: 1.00% or less, Ni: 0.50% or less, Cu: 0.50% or less, B: 0.0200% or less, V: 0.100% or less, Mo: 0.20% or less, W: 0.10% or less, Bi: 0.100% or less, Ca: 0.0100% or less, Mg: 0.0100% or less, REM: 0.0100% or less, and the balance: Fe and impurities; the metal structure contains 60% or more by volume of ferrite and at least one of martensite and bainite in a total amount of 5% by volume or more and less than 30% by volume; and the average crystal grain size d of the ferrite F is 10.0 μm or less.
[0010] A method for producing a cold-rolled steel sheet according to one embodiment of the present invention is a method for producing the above-mentioned cold-rolled steel sheet, and includes the steps of: heating a steel sheet subjected to cold rolling after hot rolling to a temperature T2 of 800 to 900 ° C; cooling from the temperature T2 to a temperature T3 of 750 to 850 ° C and lower than the temperature T2 at an average cooling rate CR of 3 ° C / sec or more; holding the temperature T3 for a holding time t2 of 30 to 60 seconds; and cooling to a temperature of 300 ° C or less at an average cooling rate of 20 ° C / sec or more. In the step of heating to the temperature T2, the average heating rate HR from a temperature T1 of 750 ° C or less to the temperature T2 is 100 ° C / sec or more, and the time t1 from reaching the temperature T2 to starting cooling is 10 seconds or less. Effect of the Invention
[0011] According to the present invention, a cold-rolled steel sheet having high strength and excellent workability can be obtained. [Brief description of the drawings]
[0012] [Figure 1] FIG. 1 is a diagram that illustrates a heat pattern of a heat treatment applied to a steel sheet. [Diagram 2] FIG. 2 is a diagram showing a schematic diagram of the change in the structure of the steel sheet caused by the heat treatment of FIG. [Diagram 3] FIG. 3 is a diagram shown for comparison, which is a schematic diagram showing the change in the structure of a steel plate caused by heat treatment of a general DP steel. [Figure 4] FIG. 4 is a scatter diagram showing the relationship between the tensile strength TS and the hole expansion ratio λ. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0013] The present inventors have conducted various studies to solve the above problems and have obtained the following findings.
[0014] In order to achieve both high strength and excellent workability, it is effective to have a structure that is mainly composed of soft ferrite and contains an appropriate amount of hard quenched structure (martensite or bainite), and to make the grain size of the ferrite fine. Specifically, the structure contains 60% or more by volume of ferrite and contains at least one of martensite and bainite in a total amount of 5% to 30% by volume, and the average grain size of ferrite is d F It is effective to keep the thickness at 10.0 μm or less.
[0015] As a method for obtaining such a structure, the steel sheet after cold rolling is treated with Ac 3 After heating rapidly to a temperature range above the austenite single phase point, the Ac 1 Ac above points 3 It is effective to cool the steel to a temperature range below this point (the ferrite-austenite two-phase region, hereafter sometimes simply referred to as the "two-phase region"), hold it at this temperature for a short period of time, and then rapidly cool it.
[0016] In general DP (Dual Phase) steel, the steel sheet after cold rolling is held in the dual phase region to precipitate austenite from the grain boundaries of ferrite, and then quenched to create a dual phase structure of ferrite and martensite. In this method, recrystallization and grain growth of ferrite progresses while the steel sheet is heated to the dual phase region and while it is held in the dual phase region, causing the ferrite to coarsen.
[0017] In contrast, in the method developed by the present inventors, the steel sheet after cold rolling is heated to the austenite single phase region, and the structure of the steel sheet is temporarily made into a single phase austenite structure. At this time, by rapidly heating in a specified temperature range, austenite is precipitated before the recrystallization and grain growth of ferrite progresses, and a fine single phase austenite structure is obtained. From this state, the steel sheet is cooled to the two-phase region before the grain growth of austenite progresses, and held at this temperature for a short time to obtain a structure containing fine ferrite and austenite. This structure is then rapidly cooled to obtain a structure containing fine ferrite and a quenched structure (martensite or bainite).
[0018] The present invention has been completed based on the above findings. Hereinafter, a cold rolled steel sheet according to one embodiment of the present invention will be described.
[0019] [Cold rolled steel plate] [Chemical composition] The cold-rolled steel sheet according to an embodiment of the present invention has a chemical composition as described below. In the following description, "%" for the content of an element means mass%.
[0020] C: 0.03 to 0.30% Carbon (C) improves the strength of steel. On the other hand, if the C content is too high, the elongation of the steel decreases. Therefore, the C content is 0.03 to 0.30%. The lower limit of the C content is preferably 0.05%, and more preferably 0.08%. The upper limit of the C content is preferably 0.25%, and more preferably 0.20%.
[0021] Silicon: 0.05 to 1.00% Silicon (Si) is a solid solution strengthening element, but if it is contained in excess, the hot workability of the steel decreases. Therefore, the Si content is 0.05 to 1.00%. The lower limit of the Si content is preferably 0.10%, and more preferably 0.20%. The upper limit of the Si content is preferably 0.90%, and more preferably 0.80%.
[0022] Mn: 0.10-3.00% Manganese (Mn) improves the hardenability of steel and improves its strength. On the other hand, if the Mn content is too high, the elongation of steel decreases. Therefore, the Mn content is 0.10 to 3.00%. The lower limit of the Mn content is preferably 0.20%, and more preferably 0.30%. The upper limit of the Mn content is preferably 2.80%, and more preferably 2.60%.
[0023] P:0.050% or less Phosphorus (P) is an impurity. P segregates at grain boundaries and reduces the elongation of steel. Therefore, the P content is 0.050% or less. The P content is preferably 0.040% or less, and more preferably 0.030% or less.
[0024] S: 0.020% or less Sulfur (S) is an impurity. S reduces the hot workability of steel. Therefore, the S content is 0.020% or less. The S content is preferably 0.015% or less, and more preferably 0.010% or less.
[0025] Al: 0.010 to 0.100% Aluminum (Al) is contained as a deoxidizing agent. On the other hand, if the Al content is too high, inclusions are generated and the elongation of the steel decreases. Therefore, the Al content is 0.010 to 0.100%. The lower limit of the Al content is preferably 0.015%, and more preferably 0.020%. The upper limit of the Al content is preferably 0.080%, and more preferably 0.060%.
[0026] N: 0.0100% or less Nitrogen (N) is an impurity. N reduces the elongation of steel. Therefore, the N content is 0.0100% or less. The upper limit of the N content is preferably 0.0080%, and more preferably 0.0060%. On the other hand, excessive reduction of N increases the manufacturing cost. The lower limit of the N content is preferably 0.0005%, and more preferably 0.0010%.
[0027] At least one of Ti and Nb: 0.020 to 0.150% in total Titanium (Ti) and niobium (Nb) form carbides to improve the strength of steel. Titanium carbide (TiC) and niobium carbide (NbC) also have the effect of refining austenite grains by the pinning effect. By refining the austenite grains, the grain size of martensite and bainite (prior austenite grain size) and the average crystal grain size of ferrite can be reduced. On the other hand, if the content of Ti and Nb is too high, the elongation of the steel decreases. Therefore, the cold-rolled steel sheet according to the present embodiment contains at least one of Ti and Nb, and the content of Ti and Nb is set to 0.020 to 0.150% in total. The lower limit of the total content of Ti and Nb is preferably 0.030%, more preferably 0.050%. The upper limit of the total content of Ti and Nb is preferably 0.120%, more preferably 0.100%.
[0028] The chemical composition of the cold-rolled steel sheet according to the present embodiment may contain one or more elements selected from the group consisting of Cr, Ni, Cu, B, V, Mo, W, Bi, Ca, Mg, and REM. All of these elements are optional elements. That is, the chemical composition of the cold-rolled steel sheet according to the present embodiment may not contain part or all of Cr, Ni, Cu, B, V, Mo, W, Bi, Ca, Mg, and REM.
[0029] Cr:1.00% or less Ni: 0.50% or less Cu: 0.50% or less B: 0.0200% or less Chromium (Cr), nickel (Ni), copper (Cu) and boron (B) all improve the hardenability and strength of steel. This effect can be achieved with even small amounts of Cr, Ni, Cu and B. On the other hand, excessive Cr, Ni, Cu and B contents reduce the elongation of steel. Therefore, the Cr content is 1.00% or less, the Ni content is 0.50% or less, the Cu content is 0.50% or less and the B content is 0.0200% or less.
[0030] The upper limit of the Cr content is preferably 0.60%, and more preferably 0.40%. The lower limit of the Cr content is preferably 0.01%, and more preferably 0.05%, and more preferably 0.10%.
[0031] The upper limit of the Ni content is preferably 0.40%, more preferably 0.30%. The lower limit of the Ni content is preferably 0.01%, more preferably 0.05%, more preferably 0.10%.
[0032] The upper limit of the Cu content is preferably 0.45%, more preferably 0.40%, and the lower limit of the Cu content is preferably 0.01%, more preferably 0.05%, and more preferably 0.10%.
[0033] The upper limit of the B content is preferably 0.0100%, more preferably 0.0050%, and more preferably 0.0020%. The lower limit of the B content is preferably 0.0003%, more preferably 0.0005%, and more preferably 0.0010%.
[0034] V: 0.10% or less Mo: 0.20% or less W: 0.10% or less Vanadium (V), molybdenum (Mo) and tungsten (W) all form carbides to improve the strength of steel. This effect can be achieved with even small amounts of V, Mo and W. On the other hand, excessive V, Mo and W contents reduce the elongation of steel. Therefore, the V content is 0.10% or less, the Mo content is 0.20% or less and the W content is 0.10% or less.
[0035] The upper limit of the V content is preferably 0.08%, more preferably 0.06%, and the lower limit of the V content is preferably 0.01%.
[0036] The upper limit of the Mo content is preferably 0.18%, more preferably 0.15%, and the lower limit of the Mo content is preferably 0.01%, more preferably 0.05%.
[0037] The upper limit of the W content is preferably 0.08%, more preferably 0.06%, and the lower limit of the W content is preferably 0.01%, more preferably 0.03%.
[0038] Bi:0.010% or less Bismuth (Bi) reduces microsegregation of Mn, Si, etc., and contributes to improving the bendability of steel. On the other hand, if the Bi content is excessive, the elongation of steel decreases. Therefore, the Bi content is 0.010% or less. The upper limit of the Bi content is preferably 0.008%, more preferably 0.006%. The lower limit of the Bi content is preferably 0.001%, more preferably 0.002%.
[0039] Ca:0.0100% or less Mg: 0.0100% or less REM: 0.0100% or less Calcium (Ca), magnesium (Mg) and rare earth elements (REM) all improve the hot workability of steel. This effect can be achieved even if even small amounts of Ca, Mg and REM are contained. On the other hand, excessive amounts of Ca, Mg and REM cause inclusions to form and reduce the elongation of the steel. Therefore, the Ca content is 0.0100% or less, the Mg content is 0.0100% or less and the REM content is 0.0100% or less.
[0040] The upper limit of the Ca content is preferably 0.0050%, and more preferably 0.0030%. The lower limit of the Ca content is preferably 0.0001%, and more preferably 0.0005%, and more preferably 0.0010%.
[0041] The upper limit of the Mg content is preferably 0.0050%, more preferably 0.0030%, and the lower limit of the Mg content is preferably 0.0001%, more preferably 0.0005%, and more preferably 0.0010%.
[0042] The upper limit of the REM content is preferably 0.0050%, more preferably 0.0030%. The lower limit of the REM content is preferably 0.0001%, more preferably 0.0005%, more preferably 0.0010%. Note that REM is a general term for 17 elements in total, including Sc, Y, and lanthanoids, and the REM content refers to the total amount of the above elements.
[0043] The balance of the chemical composition of the cold-rolled steel sheet according to the present embodiment is Fe and impurities. The impurities referred to here are elements that are mixed in from ores or scraps used as raw materials for steel, or elements that are mixed in from the environment during the manufacturing process. The impurities are not limited to these, but may be, for example, O.
[0044] The chemical composition of the cold-rolled steel sheet according to the present embodiment preferably has a carbon equivalent Ceq represented by the following formula (I) of 0.10 to 1.00. The lower limit of the carbon equivalent Ceq is preferably 0.20, and more preferably 0.30. The upper limit of the carbon equivalent Ceq is preferably 0.90, and more preferably 0.80. Ceq=C+(1 / 24)Si+(1 / 6)Mn+(1 / 40)Ni+(1 / 5)Cr+(1 / 4)Mo+(1 / 14)V (I) In the formula, each element symbol represents the content (mass%) of each element in the steel.
[0045] [Metal structure] The metal structure of the cold-rolled steel sheet according to the present embodiment is a structure containing 60 volume % or more of ferrite and 5 volume % or more and less than 30 volume % of at least one of martensite and bainite in total. The cold-rolled steel sheet according to the present embodiment has a structure in which a quenched structure (martensite or bainite), which is a hard structure, is dispersed in a structure mainly composed of ferrite.
[0046] The metal structure of the cold-rolled steel sheet according to the present embodiment contains 60% or more by volume of ferrite. If the volume fraction of ferrite is too low, it becomes difficult to achieve both strength and workability. Note that as the volume fraction of ferrite increases, the workability improves, but the strength tends to decrease. The upper limit of the volume fraction of ferrite is, for example, 95%.
[0047] The metal structure of the cold-rolled steel sheet according to the present embodiment includes at least one of martensite and bainite, and the total volume fraction of martensite and bainite is 5% or more and less than 30%. If the volume fraction of the quenched structure (martensite or bainite) is too low, it becomes difficult to ensure strength. On the other hand, if the volume fraction of the quenched structure is too high, workability decreases.
[0048] For example, the cold-rolled steel sheet according to the present embodiment may have a ferrite volume fraction of 80-95% and a total of martensite and bainite volume fractions of 5-15%. The cold-rolled steel sheet according to the present embodiment may also have a ferrite volume fraction of 70-80% and a total of martensite and bainite volume fractions of 15-25%. The cold-rolled steel sheet according to the present embodiment may also have a ferrite volume fraction of 60-70% and a total of martensite and bainite volume fractions of 20% or more and less than 30%.
[0049] The metal structure of the cold-rolled steel sheet according to the present embodiment may contain a small amount of structures other than ferrite, martensite, and bainite. The structures other than ferrite, martensite, and bainite are, for example, retained austenite and pearlite. The total volume fraction of the structures other than ferrite, martensite, and bainite is preferably 10% or less, more preferably 8% or less, and even more preferably 5% or less.
[0050] The cold-rolled steel sheet according to the present embodiment has an average grain size d F The average grain size of ferrite is 10.0 μm or less. F By reducing the average grain size of ferrite, the strength and workability can be improved. F The upper limit of the average grain size d of ferrite is preferably 9.5 μm, and more preferably 9.0 μm. F The lower limit is, for example, 4.0 μm.
[0051] In the cold-rolled steel sheet according to the present embodiment, preferably, the prior austenite grain size in the total volume of martensite and bainite is 0.8×d F More than 1.2×d F The ratio of martensite and bainite, which is equal to or less than 55 volume %, is 55 volume % or more.
[0052] As described above, the cold-rolled steel sheet according to this embodiment has a structure in which a hard structure, quenched structure (martensite or bainite), is dispersed in a structure mainly composed of ferrite. In order to achieve both strength and workability, it is preferable to set the volume fraction of the quenched structure within a predetermined range (5 volume % or more and less than 30 volume %), and to uniformly disperse the quenched structure having a relatively uniform grain size. Specifically, in the quenched structure, the average grain size d of ferrite is set to 1000 μm. F It is preferable to increase the proportion of grains having the same grain size (prior austenite grain size) as that of the total volume of martensite and bainite. F More than 1.2×d F By setting the ratio of martensite and bainite (hereinafter referred to as "the ratio of the hardened structure of the specific grain size") to 55 volume % or more, excellent strength and workability can be obtained. The lower limit of the ratio of the hardened structure of the specific grain size is more preferably 60 volume %, and even more preferably 70 volume %.
[0053] The cold-rolled steel sheet according to the present embodiment preferably contains at least one of TiC and NbC having a particle size of 2 to 10 nm in total of 3.0 × 10 13 pieces / cm 2 Including the above.
[0054] Both TiC and NbC have the effect of refining austenite grains through the pinning effect. By refining the austenite grains, the grain size of martensite and bainite (prior austenite grain size) and the average grain size of ferrite d F The lower limit of the total number density of TiC and NbC is more preferably 5.0×10 13 pieces / cm 2 The upper limit of the total number density of TiC and NbC is, for example, 5.0 × 10 6 pieces / cm 2 It is.
[0055] [Mechanical properties] The cold-rolled steel sheet according to the present embodiment preferably has a tensile strength TS of 590 MPa or more, a total elongation EL of 15% or more, and a hole expansion ratio λ of 20% or more.
[0056] The cold-rolled steel sheet according to the present embodiment preferably satisfies the following relational formula (A). λ≧-0.0505×TS+70.734 (A) In the above formula, TS represents the tensile strength (MPa) and λ represents the hole expansion ratio (%).
[0057] In one aspect, the cold-rolled steel sheet according to the present embodiment may have a tensile strength TS of 590 to 780 MPa, a total elongation EL of 25 to 35%, and a hole expansion ratio λ of 40 to 50%. In another aspect, the cold-rolled steel sheet according to the present embodiment may have a tensile strength TS of 780 to 980 MPa, a total elongation EL of 18 to 28%, and a hole expansion ratio λ of 30 to 40%. In yet another aspect, the cold-rolled steel sheet according to the present embodiment may have a tensile strength TS of 980 to 1180 MPa, a total elongation EL of 15 to 20%, and a hole expansion ratio λ of 20 to 30%.
[0058] In the cold-rolled steel sheet according to the present embodiment, Y1, represented by the following formula (B), is preferably from -100 to 100. Y1=18.793×A1-428.9-TS (B) Here, A1 represents the proportion (volume %) of the hardened structure with a specific grain size, and TS represents the tensile strength (MPa).
[0059] In the cold-rolled steel sheet according to the present embodiment, Y2 represented by the following formula (C) is preferably from -10 to 10. Y2=-0.6537×A1-68.045-EL (B) Here, A1 represents the proportion (volume %) of the hardened structure of a specific grain size, and EL represents the total elongation (%).
[0060] In the cold-rolled steel sheet according to the present embodiment, Y3 represented by the following formula (D) is preferably from -20 to 20. Y3=12.326×d F-72.469-λ (B) where d F represents the average grain size of ferrite (μm), and λ represents the hole expansion ratio (%).
[0061] [Method of manufacturing cold-rolled steel sheets] An example of a method for manufacturing the above-mentioned cold-rolled steel sheet will be described below. The manufacturing method described below is merely an example, and does not limit the manufacturing method of the cold-rolled steel sheet according to the present embodiment.
[0062] First, a steel sheet having the above-mentioned chemical composition and cold-rolled after hot rolling is prepared (hereinafter referred to as "base steel sheet"). The conditions of hot rolling and cold rolling are not particularly limited, and may be normal conditions. Heat treatment or the like may be performed between the hot rolling and cold rolling.
[0063] Fig. 1 is a diagram showing a typical heat pattern of a heat treatment applied to a base steel sheet. Fig. 1 is a diagram for explanatory purposes, and the lengths and inclinations of the lines do not necessarily accurately reflect the actual temperatures, holding times, heating rates, cooling rates, etc.
[0064] First, the steel sheet is heated to a temperature T2 of 800 to 900°C. At this time, the average heating rate HR from temperature T1 to temperature T2 is set to 100°C / sec or more. Temperature T1 is 750°C or less. The heating rate to temperature T1 may be any rate. Next, the steel sheet is cooled at an average cooling rate CR of 3°C / sec or more to a temperature T3 that is 750 to 850°C and lower than temperature T2. At this time, the time t1 from when the steel sheet reaches temperature T2 to when cooling starts is set to 10 seconds or less. After cooling to temperature T3, the steel sheet is held at temperature T3 for a holding time t2 of 30 to 60 seconds. After that, the steel sheet is cooled to a temperature of 300°C or less at an average cooling rate of 20°C / sec or more.
[0065] Fig. 2 is a diagram showing a change in the structure of a steel sheet by the above-mentioned heat treatment. Fig. 3 is a diagram shown for comparison, which shows a change in the structure of a steel sheet by the heat treatment of a general DP steel. In Fig. 2 and Fig. 3, "α" represents ferrite, "γ" represents austenite, and "M / B" represents martensite and / or bainite.
[0066] In normal DP (Dual Phase) steel, the steel sheet after cold rolling is held in the dual-phase region to precipitate austenite from the grain boundaries of ferrite, and then quenched to form a dual-phase structure of ferrite and martensite (or bainite), as shown in Figure 3. In this method, recrystallization and grain growth of ferrite progresses while the steel sheet is heated to the dual-phase region and while it is held in the dual-phase region, causing the ferrite to coarsen.
[0067] In contrast, as shown in Fig. 2, in the heat treatment according to the present embodiment, the steel sheet after cold rolling is heated to a temperature T2, and the structure of the steel sheet is temporarily made into a single-phase structure of austenite. At this time, by rapidly heating from temperature T1 to temperature T2, austenite is precipitated before the recrystallization and grain growth of ferrite progresses, and a fine single-phase structure of austenite is made. From this state, it is cooled to temperature T3 before the grain growth of austenite progresses, and is held at this temperature T3 for a holding time t2, thereby making a structure containing fine ferrite and austenite. This structure is rapidly cooled to make a structure containing fine ferrite and a quenched structure (martensite or bainite).
[0068] The temperature T2 is 800 to 900°C. If the temperature T2 is too low, there will be no time during the heat treatment process for the austenite to become a single-phase structure, and the intended structure will not be obtained. Specifically, the steel sheet after heat treatment will contain a mixture of ferrite that has been present since room temperature and ferrite that precipitated during holding at temperature T3. The ferrite that has been present since room temperature is held at high temperature for a longer time, so its grain size will be larger than that of the ferrite that precipitated during holding at temperature T3. On the other hand, if the temperature T2 is too high, the austenite will coarsen. When the austenite coarsens, the density of the grain boundaries that become the ferrite precipitation sites will decrease, so that when ferrite is generated to a predetermined volume fraction, the size of each ferrite grain will increase. That is, the average crystal grain size d of ferrite F In addition, the grain size of martensite or bainite also increases.
[0069] The temperature T2 is preferably 830° C. or higher, more preferably 860° C. or higher. The temperature T2 is preferably 3 It is above points.
[0070] In the process of heating the base steel sheet to temperature T2, the steel sheet is rapidly heated in the temperature range from temperature T1 to temperature T2. Temperature T1 is 750°C or less, and the average heating rate HR from temperature T1 to temperature T2 is 100°C / sec or more. Such rapid heating can be achieved, for example, by high-frequency induction heating (IH heating).
[0071] If temperature T1, i.e., the temperature at which rapid heating begins, is too high, ferrite recrystallization and grain growth will proceed before temperature T1 is reached. Also, if the average heating rate HR, i.e., the heating rate during rapid heating, is too low, ferrite recrystallization and grain growth will proceed before temperature T2 is reached. As ferrite recrystallization and grain growth proceed, the density of the grain boundaries that serve as austenite precipitation sites decreases, and the size of each austenite grain increases when a single-phase austenite structure is formed at temperature T2. As mentioned above, when austenite grains coarsen, the average crystal grain size d of ferrite after heat treatment decreases. F will also become larger.
[0072] The temperature T1 is preferably 700° C. or less, more preferably 650° C. or less. The temperature T1 is preferably Ac 1 The temperature T1 is preferably equal to or lower than the recrystallization starting temperature, and more preferably equal to or lower than the recrystallization starting temperature. The lower limit of the temperature T1 is not particularly limited, but is, for example, 600° C. The average heating rate HR is preferably equal to or higher than 200° C. / sec, more preferably equal to or higher than 600° C. / sec, and even more preferably equal to or higher than 1100° C. / sec. The heating rate up to the temperature T1 may be any rate, and is not particularly limited, but may be, for example, equal to or lower than 10° C. / sec.
[0073] Time t1, i.e., the time from reaching temperature T2 to starting cooling, is 10 seconds or less. If time t1 is too long, austenite grains become coarse. Time t1 is preferably 8 seconds or less, more preferably 6 seconds or less. The lower limit of time t1 is not particularly limited, but is, for example, 1 second.
[0074] The average cooling rate CR, i.e., the average cooling rate from temperature T2 to temperature T3, is 3°C / sec or more. If the average cooling rate CR is too small, the grain growth of austenite progresses before the temperature T3 is reached. The average cooling rate CR is preferably 7°C / sec or more, more preferably 15°C / sec or more. The upper limit of the average cooling rate CR is not particularly limited, but is, for example, 100°C / sec.
[0075] Temperature T3 is 750 to 850°C and is lower than temperature T2. If temperature T3 is too low or too high, a structure having a predetermined amount of ferrite cannot be obtained. Temperature T3 is preferably less than 800°C, and more preferably 790°C or less. The lower limit of temperature T3 is preferably 760°C, more preferably 770°C, and even more preferably 780°C. Temperature T3 is preferably at a temperature of Ac 1 Ac above points 3 It is less than a point.
[0076] The holding time t2, that is, the holding time at the temperature T3, is 30 to 60 seconds. If the holding time t2 is too short, a structure having a predetermined amount of ferrite cannot be obtained. On the other hand, if the holding time t2 is too long, the average grain size d of ferrite becomes too small. F The upper limit of the retention time t2 is preferably 50 seconds, and more preferably 40 seconds.
[0077] After being held at temperature T3 for holding time t2, the material is cooled to a temperature of 300°C or less at an average cooling rate of 20°C / sec or more. If the cooling rate is too slow or the cooling stop temperature is too high, the desired amount of hardened structure (martensite or bainite) cannot be obtained. The average cooling rate from temperature T3 is preferably 30°C / sec or more, more preferably 40°C / sec or more. The upper limit of the cooling stop temperature is preferably 270°C, more preferably 250°C.
[0078] Through the above steps, the cold-rolled steel sheet according to this embodiment is manufactured.
[0079] In one embodiment of the heat treatment, the temperature T1 may be 700 to 750°C, the temperature T2 may be 860 to 900°C, the average heating rate HR may be 200 to 700°C / sec, the average cooling rate CR may be 3 to 7°C / sec, and the holding time t2 may be 50 to 60 seconds. In this case, the volume fraction of ferrite is 80 to 95%, the total volume fraction of martensite and bainite is 5 to 15%, and the average grain size d of ferrite is 100 to 150°C. F The cold-rolled steel sheet has a tensile strength TS of 590 to 780 MPa, a total elongation EL of 25 to 35%, and a hole expansion ratio λ of 40 to 50%.
[0080] In another embodiment of the heat treatment, the temperature T1 may be 650 to 700°C, the temperature T2 may be 830 to 860°C, the average heating rate HR may be 600 to 1200°C / sec, the average cooling rate CR may be 7 to 15°C / sec, and the holding time t2 may be 40 to 50 seconds. In this case, the volume fraction of ferrite is 70 to 80%, the total volume fraction of martensite and bainite is 15 to 25%, and the average grain size d of ferrite is 1.0 to 1.0 mm. F The cold-rolled steel sheet has a tensile strength TS of 780 to 980 MPa, a total elongation EL of 18 to 28%, and a hole expansion ratio λ of 30 to 40%.
[0081] In another embodiment of the heat treatment, the temperature T1 may be 600 to 650°C, the temperature T2 may be 800 to 830°C, the average heating rate HR may be 1100 to 1500°C / sec, the average cooling rate CR may be 15 to 50°C / sec, and the holding time t2 may be 30 to 40 seconds. In this case, the volume fraction of ferrite is 60 to 70%, the total volume fraction of martensite and bainite is 20% or more and less than 30%, and the average grain size d of ferrite is 100 to 1500°C / sec. F A cold-rolled steel sheet having a grain size of 7.5 to 9.0 μm and a ratio of a hardened structure having a specific grain size of 70 to 80 volume % is obtained. This cold-rolled steel sheet has a tensile strength TS of 980 to 1180 MPa, a total elongation EL of 15 to 20%, and a hole expansion ratio λ of 20 to 30%.
[0082] The heat treatment conditions according to these embodiments, and the structures and mechanical properties of the cold-rolled steel sheets obtained by these heat treatments are summarized in Table 1. These heat treatment embodiments are merely examples, and the heat treatment conditions are not limited to these embodiments.
[0083] [Table 1]
[0084] The cold-rolled steel sheet and the manufacturing method thereof according to one embodiment of the present invention have been described above. According to this embodiment, a cold-rolled steel sheet having high strength and excellent workability can be obtained. EXAMPLES
[0085] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples.
[0086] The hot rolling was followed by cold rolling to produce steel sheets having the chemical compositions shown in Table 2. However, for test number 25, the steel sheet was produced by only hot rolling. This steel sheet was subjected to heat treatment under the conditions shown in Table 3. After being held at temperature T3 for holding time t2, it was cooled to room temperature at a cooling rate of 20°C / s.
[0087] [Table 2]
[0088] [Table 3]
[0089] The heat-treated test materials were subjected to microstructural observation, tensile testing, and hole expansion testing.
[0090] To evaluate the tensile properties, two JIS No. 5 test pieces were taken from each heat-treated test material with the longitudinal direction parallel to the rolling direction (L direction) and tested at a tensile speed of 10 mm / min. From the results, the tensile strength TS (MPa) and total elongation EL (%) were calculated. The tensile strength TS and total elongation EL were calculated as the average of the two tensile test pieces.
[0091] To measure the hole expansion ratio, two 90 mm × 90 mm test pieces were taken from the heat-treated test material, and the initial hole diameter d 0 A punched hole of 10 mm was created. This hole was expanded using a conical punch with a tip angle of 60°. When a crack appeared at the punched end and penetrated the plate thickness, the expansion was stopped and the load was removed. The hole diameter of the test piece was measured in two directions: parallel to the rolling direction, perpendicular to the rolling direction, and at an angle of 45°, and the average value was taken as the hole diameter d after hole expansion. The hole expansion ratio λ was evaluated using the following formula. The hole expansion ratio λ was taken as the average of the two test pieces. λ(%)=(dd0 ) / d 0 ×100
[0092] The metal structure of the test material after the heat treatment was measured by the following method.
[0093] First, a specimen was taken from the heat-treated test material so that the cross section parallel to the rolling direction and the plate thickness direction was the observation surface. EBSD (Electron Backscatter Diffraction) analysis was performed in an area of 200 μM × 100 μmT on the L cross section (cross section parallel to the rolling direction and the plate thickness direction) of the test material. The scan step was 0.1 μm, and the measurement points were in a hexagonal grid.
[0094] When the EBSD data was analyzed and the crystalline phase was identified from the EBSD pattern at the measurement point, the areas identified as BCC phase were regarded as either martensite, bainite or ferrite, the areas identified as FCC phase were regarded as retained austenite, and the areas where the structure could not be identified (for example, when the Confidential Index value was less than 0.1 in the TSL EBSD system) were regarded as cementite contained in pearlite, etc.
[0095] In the EBSD data, boundaries with a crystal orientation difference of 15° or more were defined as grain boundaries, and the areas surrounded by grain boundaries were considered as crystal grains.
[0096] The percentages of the measurement points of BCC phases other than ferrite (martensite or bainite) and the measurement points of ferrite were calculated to determine the total volume fraction of martensite and bainite and the volume fraction of ferrite, respectively. The remaining regions included pearlite and retained austenite (regions identified as FCC phases based on EBSD) and were classified as other regions.
[0097] Average grain size of ferrite d F was obtained by calculating the average value of the circle equivalent diameter d from the following equation in the EBSD measurement.
[0098]
number
[0099] Here, A i is the area of the i-th ferrite analyzed in the EBSD data, and d i is the circle equivalent diameter of the i-th ferrite. The circle equivalent diameter is the area of the i-th ferrite (= A i ) means the diameter of a circle having an area equal to
[0100] The "proportion of hardened structure of a specific grain size" is the BCC phase (martensite or bainite) other than ferrite, with a circle equivalent diameter of 0.8 x d F More than 1.2×d F The area was calculated by dividing the total area of those phases that were equal to or less than ferrite by the total area of the BCC phase (martensite or bainite) other than ferrite.
[0101] The number density of TiC and NbC in the test material after heat treatment was measured as follows. Samples were taken and embedded in resin so that the vertical cross section to the rolling direction was the object of observation. The number of precipitates was counted by observation with an electron microscope using the extraction replica method. 2 The area was observed from 10 visual fields, and the number density of TiC and NbC particles with particle sizes of 2 to 10 nm was measured.
[0102] The results are shown in Tables 4 and 5.
[0103] [Table 4]
[0104] [Table 5]
[0105] FIG. 4 is a scatter diagram showing the relationship between the tensile strength TS and the hole expansion ratio λ. The white marks indicate the average grain size d FThe data are for test materials with an average grain size of ferrite of 10.0 μm or less. The solid marks indicate the average grain size of ferrite d F As shown in Fig. 4, the average grain size of ferrite d F It can be seen that by setting the average grain size of ferrite d to 10.0 μm or less, the hole expansion ratio λ can be increased when compared at the same tensile strength TS. F By keeping the grain size at 10.0 μm or less, it is possible to achieve a higher level of both high strength and excellent processability.
[0106] Although the embodiment of the present invention has been described above, the above-mentioned embodiment is merely an example for carrying out the present invention. Therefore, the present invention is not limited to the above-mentioned embodiment, and the above-mentioned embodiment can be appropriately modified and carried out without departing from the spirit of the present invention.
Claims
1. The chemical composition, in mass%, is C: 0.03 to 0.30%, Si: 0.05-1.00%, Mn: 0.10-3.00%, P: 0.050% or less, S: 0.020% or less, Al: 0.010-0.100%, N: 0.0100% or less, At least one of Ti and Nb: 0.020 to 0.150% in total, The balance is Fe and impurities. The metal structure contains 60 volume % or more of ferrite and 5 volume % or more but less than 30 volume % of at least one of martensite and bainite in total, The average grain size of the ferrite d F The cold-rolled steel sheet has a grain size of 10.0 μm or less.
2. The chemical composition, in mass%, is C: 0.03 to 0.30%, Si: 0.05-1.00%, Mn: 0.10-3.00%, P: 0.050% or less, S: 0.020% or less, Al: 0.010-0.100%, N: 0.0100% or less, At least one of Ti and Nb: 0.020 to 0.150% in total; Further, one or more selected from the group consisting of Cr: 1.00% or less, Ni: 0.50% or less, Cu: 0.50% or less, B: 0.0200% or less, V: 0.100% or less, Mo: 0.20% or less, W: 0.10% or less, Bi: 0.010% or less, Ca: 0.0100% or less, Mg: 0.0100% or less, and REM: 0.0100% or less; The balance is Fe and impurities. The metal structure contains 60 volume % or more of ferrite and 5 volume % or more but less than 30 volume % of at least one of martensite and bainite in total, The average grain size of the ferrite d F The cold-rolled steel sheet has a grain size of 10.0 μm or less.
3. The cold-rolled steel sheet according to claim 1 or 2, Of the total volume of the martensite and bainite, the prior austenite grain size is 0.8×d F Above 1.2 x d F The cold-rolled steel sheet has a ratio of martensite and bainite of 55 volume % or more.
4. The cold-rolled steel sheet according to claim 1 or 2, At least one of TiC and NbC having a particle size of 2 to 10 nm is mixed in a total of 3.0 × 10 13 pieces / cm 2 Cold rolled steel sheet including above.
5. A method for producing the cold-rolled steel sheet according to claim 1 or 2, A step of heating the hot-rolled and then cold-rolled steel sheet to a temperature T2 of 800 to 900 ° C.; cooling the steel sheet from temperature T2 to a temperature T3 that is 750 to 850° C. and is lower than temperature T2 at an average cooling rate CR of 3° C. / sec or more; A step of maintaining the temperature T3 for a maintenance time t2 of 30 to 60 seconds; and cooling the resulting mixture to a temperature of 300° C. or less at an average cooling rate of 20° C. / s or more; In the step of heating to the temperature T2, an average heating rate HR from a temperature T1, which is 750° C. or less, to the temperature T2 is 100° C. / sec or more; The method for producing a cold-rolled steel sheet, wherein the time t1 from when the temperature T2 is reached to when cooling is started is 10 seconds or less.
Citation Information
Patent Citations
Resin composition for molding
JP1986019655A
High-tensile cold-rolled steel sheet and method for manufacturing the same
JP4292986B2
Steel plates, components, and their manufacturing methods
JP7006849B1